Occurrence of Thermophilic Microorganisms in Different Full Scale Biogas Plants - Kushkevych, Ivan; Cejnar, Jiří; Vítězová, Monika; Vítěz, Tomáš; Dordević, Dani; Bomble, Yannick J (International journal of molecular sciences, 2019)
BACKGROUND: In recent years, various substrates have been tested to increase the sustainable production of biomethane. The effect of these substrates on methanogenesis has been investigated mainly in small volume fermenters and were, for the most part, focused on studying the diversity of mesophilic microorganisms. However, studies of thermophilic communities in large scale operating mesophilic biogas plants do not yet exist. METHODS: Microbiological, biochemical, biophysical methods, and statistical analysis were used to track thermophilic communities in mesophilic anaerobic digesters. RESULTS: The diversity of the main thermophile genera in eight biogas plants located in the Czech Republic using different input substrates was investigated. In total, 19 thermophilic genera were detected after 16S rRNA gene sequencing. The highest percentage (40.8%) of thermophiles was found in the Modřice biogas plant where the input substrate was primary sludge and biological sludge (50/50, w/w %). The smallest percentage (1.87%) of thermophiles was found in the Čejč biogas plant with the input substrate being maize silage and liquid pig manure (80/20, w/w %). CONCLUSIONS: The composition of the anaerobic consortia in anaerobic digesters is an important factor for the biogas plant operator. The present study can help characterizing the impact of input feeds on the composition of microbial communities in these plants.
Keywords: RNA ribozomální 16S; Microbial Consortia; thermophilic microorganisms; biopaliva; Anaerobiosis; renewable energy; RNA, Bacterial; Biofuels; anaerobióza; odpadní vody; bakteriální RNA; Sewage; anaerobic digesters; biogas; RNA, Ribosomal, 16S; Illumina sequencing; mikrobiální společenstva